Diagnosis of Neuropathic Pain in the Orofacial Region - Imamura, Yoshiki; Noma, Noboru; Okada, Akiko (Japanese Journal of Orofacial Pain, 2011)
Dentists may encounter difficulties when they diagnose unknown orofacial pain especially after dental practice including extraction and endodontic treatment. Neuropathic pain is defined as pain caused by a lesion or disease of the somatosensory nervous system. Activation of nociceptive afferents by actually or potentially tissue-damaging stimuli and activity generated within the nervous system without adequate stimulation of its peripheral sensory endings may elicit pain. Special Interest Group of Neuropathic Pain of the International Association for the Study of Pain has proposed diagnostic criteria and an algorithm for the diagnosis of neuropathic pain. If pain distribution and history suggest relevant lesions or diseases, dentists are recommended to apply confirming tests, e.g., somatosensory, laboratory and objective tests. McGill pain questionnaire will help in drawing the characteristics of unknown pain. Dentists may employ qualitative sensory tests (e.g., brush sweeping and pin prick) to uncover the affected region. Hypoesthesia, allodynia, hyperalgesia and dysesthesia are essential sensory changes after nerve injury. Hypoesthesia will be detected by light touch using fine filaments or cotton wisp. Allodynia will be observed by sweeping brush or dragging a Q-tip. Hyperalgesia will be demonstrated by pin prick. Conditions that should be ruled out in diagnosing neuropathic pain after endodontic therapy include fenestration, traumatic occlusion and referred pain from masticatory muscles.